STUDI LITERATUR: PENGARUH FISIOTERAPI DADA PADA PASIEN PNEUMONIA - Oktaviani, Vivin; Nugroho, Setiyo Adi (Jurnal Keperawatan Profesional, 2022)
Patients suffering from respiratory system disorders often experience excess mucus production, which makes breathing difficult because sputum usually accumulates until it becomes thick and difficult to expel. Chest physiotherapy can be applied to remove sputum for a more effective airway. The purpose of this study of literature review is to evaluate the effect of chest physiotherapy on pneumonia patients. Database searches included ScienceDirect, Pubmed, Google Scholar with keywords chest physiotherapy and pneumonia. The criteria for selected articles are 2017-2021, with full text and in English and Indonesian. This study of literature used 18 articles that met the inclusion criteria. Chest physiotherapy can facilitate sputum production, improve respiratory rate and provide an airway. This technique can be applied to increase the effectiveness of the airway.